Confounding factors in vesicle uptake studies using fluorescent lipophilic membrane dyes - Takov, Kaloyan; Yellon, Derek M.; Davidson, Sean M. (Journal of extracellular vesicles, 2017)
Small extracellular vesicles (sEVs) such as exosomes are nanocarriers of proteins, RNAs and DNAs. Isolation of pure sEV populations remains challenging, with reports of protein and lipoprotein contaminants in the isolates. Cellular uptake - a cornerstone for understanding exosome and sEV function - is frequently examined using lipophilic dyes such as PKH67 or CellMask to label the vesicles. In this study, we investigated whether contaminants can confound the outcomes from sEV and exosomes uptake experiments. sEVs were isolated from blood plasma of fasted or non-fasted rats as well as from serum-supplemented or serum-free conditioned cell culture medium using size-exclusion chromatography (SEC). Eluent fractions were characterized using nanoparticle tracking, protein and triglyceride assays and immunoassays. SEC fractions were labelled with different lipophilic dyes and cellular uptake was quantified using endothelial cells or primary cardiomyocytes. We report co-isolation of sEVs with apolipoprotein B-containing lipoproteins. Cellular dye transfer did not correspond to sEV content of the SEC fractions, but was severely affected by lipoprotein and protein content. Overnight fasting of rats decreased lipoprotein content and also decreased dye transfer, while late, sEV-poor/protein-rich fractions demonstrated even greater dye transfer. The potential for dye transfer to occur in the complete absence of sEVs was clearly shown by experiments using staining of sEV-depleted serum or pure protein sample. In conclusion, proteins and lipoproteins can make a substantial contribution to transfer of lipophilic dyes to recipient cells. Considering the likelihood of contamination of sEV and exosome isolates, lipophilic dye staining experiments should be carefully controlled, and conclusions interpreted with caution.